2014
DOI: 10.1182/blood-2013-11-540526
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of bacteria-induced platelet activation is triggered by FcγRIIA, integrin αIIbβ3, and platelet factor 4

Abstract: Key Points• FcgRIIA activation is key for platelet aggregation in response to bacteria, and depends on IgG and aIIbb3 engagement.• PF4 binds to bacteria and reduces the lag time for platelet aggregation.Bacterial adhesion to platelets is mediated via a range of strain-specific bacterial surface proteins that bind to a variety of platelet receptors. It is unclear how these interactions lead to platelet activation. We demonstrate a critical role for the immune receptor FcgRIIA, aIIbb3, and Src and Syk tyrosine k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
156
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(167 citation statements)
references
References 49 publications
6
156
4
Order By: Relevance
“…The addition of plasma concentrations of fibrinogen to the gel filtered platelets failed to restore aggregation however addition of plasma concentrations of purified IgG fully restored platelet aggregation. More recently, Arman et al, demonstrated that S. sanguinis, S. gordonii but not S. pneumoniae require IgG's to induce platelet aggregation [69]. The site that IgG binds to was not identified in this study.…”
Section: Indirect Interaction With Fcγriiacontrasting
confidence: 58%
See 3 more Smart Citations
“…The addition of plasma concentrations of fibrinogen to the gel filtered platelets failed to restore aggregation however addition of plasma concentrations of purified IgG fully restored platelet aggregation. More recently, Arman et al, demonstrated that S. sanguinis, S. gordonii but not S. pneumoniae require IgG's to induce platelet aggregation [69]. The site that IgG binds to was not identified in this study.…”
Section: Indirect Interaction With Fcγriiacontrasting
confidence: 58%
“…FcγRIIA is fast becoming the most important receptor in platelet bacterial interactions as it has been shown to inhibit all bacterial induced platelet activation including those triggered by S. aureus, S. epidermidis, S. sanguinis, S. gordonii, Streptococcus pneumonia, Streptococcus oralis, H. pylori and S. pyogenes [30,33,34,36,50,53,[66][67][68][69][70]. A key observation is that IgG is required for all of these bacteria to induce platelet aggregation, however antibody alone was not enough to trigger aggregation / activation of platelets.…”
Section: Indirect Interaction With Fcγriiamentioning
confidence: 99%
See 2 more Smart Citations
“…Arman and colleagues evaluated the effect of 5 bacterial strains belonging to the Staphylococcus and Streptococcus family on their ability to activate human platelets. 1 They show that the interaction of bacteria with platelets requires the platelet FcgRIIA receptor because the inhibition of FcgRIIA by monoclonal antibody IV.3 blocks platelet activation. They also show the requirement of plasma IgG and engagement of integrin by fibrinogen for the bacteria to induce platelet activation.…”
mentioning
confidence: 99%